Results after revision of the stem in periprosthetic fractures of the hip - POGLIACOMI, FRANCESCO; Corsini, Tiziana; Zanelli, Matteo; Ditta, Alessandro; Pompili, Massimo; Pedrazzini, Alessio; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2014)
Periprosthetic femoral fractures following primary total hip arthroplasty (THA) represent an emerging challenge for the orthopaedic surgeon, because of their increasing incidence and negative impact on clinical and functional patient outcome. For these reasons, in the last decade, many efforts were made to prevent and manage this complication and a large number of studies were focused on finding out the best treatment. The type of treatment depends on several factors such as morphology and location of the fracture, implant stability, quality and quantity of bone stock, patient’s age and clinical conditions. Fractures that cause loosening of the stem always require its revision, with a contextual assessment of the quality and quantity of remaining bone stock, which is generally good in type B2 and poor in type B3 according to Vancouver’s classification. The latter may require the use of bone grafts. In this context, the authors performed the following study and analyzed the results of 45 patients treated surgically for periprosthetic femoral fractures with revision of the femoral stem during a fourteen years period, between June 1999 and June 2013.